Elective Subject Recommendation System - Sangam, Savita; Uchagaonkar, Riya; Yayavaram, Sridhari; Chavan, Minal (International Journal of Computer Sciences and Engineering, 2020)
Giving students a chance to select a subject of their choice is becoming popular day by day. Elective subjects provide this chance and are increasingly a key part of the progress of a student in their academics. Various universities offer different subjects which belong to various areas of studies. Opting for the best field of study definitely plays a driving role in every student’s career. The proposed system titled “Elective Subject Recommendation System” is a web application for suggesting the best elective subject, among all their academic elective subjects, in which that particular student could have a scope of scoring more. It mainly focuses on the tests that will be taken to analyze the student’s basic knowledge in the respective field. Then the elective subject is recommended using the random forest algorithm. The objective of the project is to let every student opt the elective subjects based on their capability and knowledge but not by the choice of their fellow students.